GENETIC ANALYSIS OF QUALITATIVE AND QUANTITATIVE TRAITS AMONG PROGENIES OF ENSET CLONES ORIGINATED FROM SOUTHERN ETHIOPIA - Abraham Bosha; Mesfin Kebede Gessese (Indonesian Journal of Agricultural Science, 2021)
The present cultivated enset (Ensete ventricosum) clonal landraces in Ethiopia originated from few wild progenitors. However, enset has a mixed mode of reproduction in which, the wild enset reproduces sexually through seeds, while cultivated enset is generally propagated vegetatively. The objectives of this study were to determine the genetic structure of enset cultivars through genetic analysis of qualitative morphological traits and estimate their genetic variability by evaluating the quantitative agronomic traits data generated from progenies of cultivated and wild enset genotypes. Hence, seeds collected from six cultivated and four wild enset genotypes were used for this study. Data on four qualitative and six quantitative morphological traits were recorded from the progenies of the 10 enset genotypes. Progenies of seven enset genotypes segregated in a 3:1 segregation ratio while progenies of the remaining genotypes segregated differently for the qualitative traits considered. With regard to the quantitative traits, the progenies of the 10 enset genotypes differed significantly for five of the six traits except pseudostem length. The cultivated clones, in general performed better than that of the wild types. Moderate heritability (h2b) estimates and high genetic advances were obtained for leaf length (0.38, 62.0%), pseudostem circumference (0.35, 78.5%), and plant height (0.30, 19.1%) indicating selection for these traits indirectly improves economic yield of enset clones. This study demonstrated the possibility of creating genetic variation through selfing the existing enset genotypes for traits of interest and making improvements either through selection or crossing the elite types to develop novel enset cultivars.